2019
DOI: 10.1021/acsomega.8b03160
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Luminescence and X-ray Absorption Capacity of Eu3+:LaF3 Nanoparticles by Bi3+ Codoping

Abstract: Bi3+ codoping has been proposed in this work with a twofold objective, namely, enhancing the luminescence emission of Eu3+:LaF3 nanoparticles (NPs) and increasing their X-ray attenuation capacity, with the purpose of obtaining a bimodal bioprobe for luminescence bioimaging and X-ray computed tomography. The synthesis method, reported here for the first time for LaF3 particles, allowed obtaining uniform, nonaggregated NPs using a homogeneous precipitation in polyol medium at room temperature in just 2 h. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A small amount of Bi 3+ doped into RE‐1 structure absorbs the high energy from X‐ray, which enhances the structure perfection, promotes the exciton localization, and further improves the XEL performance as well as the photoluminescence quantum yield (PLQY). [ 17,28,36,55 ]…”
Section: Figurementioning
confidence: 99%
“…A small amount of Bi 3+ doped into RE‐1 structure absorbs the high energy from X‐ray, which enhances the structure perfection, promotes the exciton localization, and further improves the XEL performance as well as the photoluminescence quantum yield (PLQY). [ 17,28,36,55 ]…”
Section: Figurementioning
confidence: 99%
“…More interestingly, the slope of the obtained straight line for our systems was very similar (29.6 HU/mg cm –3 for DyVO 4 and 29.1 HU/mg cm –3 for HoVO 4 ) and much higher than that for iohexol (12.7 HU/mg cm –3 ), an iodine-based probe, indicating that a lower dose of our Dy- or Ho-based CA is required to obtain a similar contrast, which should be favorable for the patient. The higher X-ray attenuation capacity of our CAs when compared with iohexol can be attributed to the higher atomic number of Dy ( Z = 66) and Ho ( Z = 67), as compared with that of I ( Z = 53), since it is well-known that the X-ray attenuation coefficient increases with the fourth power of Z . The similar Z value for Dy and Ho therefore justifies the similar X-ray attenuation properties of the Dy- and Ho-based samples.…”
Section: Resultsmentioning
confidence: 51%
“…The higher X-ray attenuation capacity of our CAs when compared with iohexol can be attributed to the higher atomic number of Dy (Z = 66) and Ho (Z = 67), as compared with that of I (Z = 53), since it is wellknown that the X-ray attenuation coefficient increases with the fourth power of Z. 25 The similar Z value for Dy and Ho therefore justifies the similar X-ray attenuation properties of the Dy-and Ho-based samples. Magnetic properties.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…The observed decrease in emission intensities above 3 at% concentration of Eu 3+ in the codoped sample is accounted for by the concentration quenching effect and is a sign of the existence of energy transfer between Bi 3+ to Eu 3+ . [ 52,53 ] The existence of energy transfer phenomena is demonstrated by the spectral overlap graph between emission spectra of La 2 Zr 2 O 7 :0.5 at% Bi 3+ and excitation spectra of La 2 Zr 2 O 7 :3 at% Eu 3+ which is depicted as Figure 6d. It was observed that, the emission pattern of Bi 3+ in host overlap with the excitation spectra of Eu 3+ strongly confirms the efficient energy transfer between Bi 3+ and Eu 3+ in the host lattice (Figure 6d).…”
Section: Resultsmentioning
confidence: 98%